THE RELATIONSHIP BETWEEN STRESS AND NUTRITIONAL STATUS OF STUDENTS IN INDONESIA: A CROSS-SECTIONAL STUDY - Said, Nurhazizah Br; Ismah, Zata; Aisyah, Siti (Lembaga Penelitian dan Terapan untuk Kesehatan Jiwa (Lenterakaji), 2025)
Background: Nutritional status is the condition of the body caused by food intake and nutrient utilization. The categories of nutritional status are undernutrition, normal nutrition, and over nutrition. Nutritional status can be categorized in various ways, including using the body mass index (BMI). Purpose: was to determine the relationship between stress and nutritional status of university students. Methods: This research design used a cross-sectional design due to the analysis of this research which. The population in this study were students of the Faculty of Public Health, State Islamic University of North Sumatra. The sample was done by random sampling which amounted to 210 respondents. This research was conducted at the Faculty of Public Health, State Islamic University of North Sumatra in July 2024. The research data collected were processed using SPSS version 21 with Univariate and Bivariate tests. Collecting research data using the SRQ 29 (Self-Reporting Questionnaire) questionnaire developed by WHO. Results: There is a relationship between stress and the nutritional status of students (p-value = 0.003). Conclusion: Stress affects the nutritional status of students even though there are other factors that can affect the nutritional status of students such as diet, physical activity, and others Abstrak Latar Belakang: Status gizi ialah kondisi tubuh yang disebabkan oleh asupan makanan dan pemakaian zat gizi. Kategori dari status gizi terdiri dari gizi buruk, gizi normal, dan gizi lebih. Pengelompokan status gizi bisa menggunakan berbagai cara, termasuk memakai indeks massa tubuh (IMT). Tujuan: Untuk mengetahui hubungan stress dengan status gizi mahasiswa. Metode: Desain penelitian ini memakai desain cross sectional dikarenakan penelitian ini merupakan penelitian analisis Populasi didalam penelitian ini merupakan mahasiswa Fakultas Kesehatan Masyarakat Universitas Islam Negeri Sumatera Utara. Pengambilan sampel dilakukan dengan cara random sampling yang berjumlah 210 orang responden. Penelitian ini dilakukan di Fakultas Kesehatan Masyarakat Universitas Islam Negeri Sumatera Utara pada bulan juli 2024. Data penelitian yang terkumpul diolah menggunakan SPSS versi 21 dengan uji Univariat dan Bivariat. Pengumpulan data penelitian dengan menggunakan kuesioner SRQ 29 (Self-Reporting Questionnaire) yang dikembangkan oleh WHO. Hasil: Hasil dari penelitian ini adalah terdapat hubungan antara stress dengan status gizi mahasiswa (p-value = 0,003). Kesimpulan: Stres mempengaruhi status gizi mahasiswa walaupun ada faktor lain yang bisa mempengaruhi status gizi mahasiswa seperti pola makan, aktivitas fisik, dan lainnya.